Early Cretaceous coral biostromes from the Neuquén Basinb west-central Argentina: blooms of soft substrate forms developed under mixed clastic settings - Lazo, Dario Gustavo (2013)
Scleractinian corals were significant elements of Cretaceous shallow marine settings all over the world. In particular, they were especially important in the Tethys region where they form extended framework reef facies. Northern hemisphere forms have been intensively studied, while southern faunas are generally poorly known. Most of the occurrences of Argentine Jurassic and Cretaceous corals seem to correspond to lenticular and lentiform coral-dominated beds while framework reefs are not well-represented in contrast to Tethys occurrences. In this work an integrate analysis of a number of coral biostromes recorded from the Lower Cretaceous Agrio Formation of the Neuquén Basin is presented. It includes taxonomic, taphonomic, and palaeoecological aspects of the coral association and a detailed facies analysis. Previous studies had described six Valanginian-Hauterivian scleractinian species while recent taxonomic revision has recognized in addition at least five species. When palaeoenvironmental conditions were suitable corals developed opportunistic and short-lived meadows composed by massive, lamellar and ramose colonies, on soft substrates in mixed clastic-carbonate settings with moderate turbidity and low to moderate sedimentation rate. Calicular arranges include cerioid, thamnasterioid, meandroid, phaceloid and plocoid. Coral biostromes usually alternate with soft substrate mollusk dominated biofacies.